2017
DOI: 10.2196/cardio.8025
|View full text |Cite
|
Sign up to set email alerts
|

My Hypertension Education and Reaching Target (MyHEART): Development and Dissemination of a Patient-Centered Website for Young Adults with Hypertension

Abstract: Background Young adults (18 to 39 years old) with hypertension have the lowest rates of blood pressure control (defined as blood pressure less than 140/90 mmHg) compared to other adult age groups. Approximately 1 in 15 young adults have high blood pressure, increasing their risk of future heart attack, stroke, congestive heart failure, and/or chronic kidney disease. Many young adults reported having few resources to address their needs for health education on managing cardiovascular risk. Objective The goal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 35 publications
0
7
0
3
Order By: Relevance
“…Patient education is a common effective nonmedication therapy for HTN [ 2 ]. There are many methods of patient education effective for HTN, such as the traditional doctor's face-to-face education [ 3 ], pharmacist education [ 4 ], nurse teaching session [ 5 ], interdisciplinary education program [ 6 ], educational booklet [ 7 ], group patient education [ 8 ], telephone follow-up education [ 9 ], tailored educational program to change behaviors [ 10 ], and modern electronic methods including the educational e-mail [ 11 ], Facebook advertisement [ 12 ], message and WeChat over the cell phone [ 13 ], and educational Internet platform [ 14 ]. Can we apply many educational methods to boost the effectiveness?…”
Section: Introductionmentioning
confidence: 99%
“…Patient education is a common effective nonmedication therapy for HTN [ 2 ]. There are many methods of patient education effective for HTN, such as the traditional doctor's face-to-face education [ 3 ], pharmacist education [ 4 ], nurse teaching session [ 5 ], interdisciplinary education program [ 6 ], educational booklet [ 7 ], group patient education [ 8 ], telephone follow-up education [ 9 ], tailored educational program to change behaviors [ 10 ], and modern electronic methods including the educational e-mail [ 11 ], Facebook advertisement [ 12 ], message and WeChat over the cell phone [ 13 ], and educational Internet platform [ 14 ]. Can we apply many educational methods to boost the effectiveness?…”
Section: Introductionmentioning
confidence: 99%
“…Three recommendations are given to improve Chinese pregnant women’s accessibility of and satisfaction with NIPT. First, the internet has been widely used in the health education program [ 35 , 36 ]. Authorities and hospitals can consider providing professional information on prenatal screening and aneuploid disorders online, such as creating official websites or apps.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the level of the patient's personal educational background, understanding a simple instruction might prove to be difficult. 31,32 Some feedbacks from patients also suggested that these educational materials could be uploaded on websites or as applications on mobile phones to have more accessibility for the patients, which may also improve the accuracy. Some studies showed that website-based delivery of preoperative education for surgery is feasible and has similar patient satisfaction compared to traditional paper-based methods.…”
Section: Discussionmentioning
confidence: 99%